2021
DOI: 10.3390/insects12121060
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Plant–Pollinator Network Structure along the Elevational Gradient of the San Francisco Peaks, Arizona

Abstract: The structural patterns comprising bimodal pollination networks can help characterize plant–pollinator systems and the interactions that influence species distribution and diversity over time and space. We compare network organization of three plant–pollinator communities along the altitudinal gradient of the San Francisco Peaks in northern Arizona. We found that pollination networks become more nested, as well as exhibit lower overall network specialization, with increasing elevation. Greater weight of genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Nonetheless, the relationship between modules and pollination syndromes has been found in studies that have determined pollinator effectiveness [ 109 ] and others that have not (e.g., [ 84 ]). Therefore, the lack of an association between modules and syndromes may be related to the presence of super-generalist pollinators in high-elevation environments [ 110 , 111 ]. The presence of these super-generalist floral visitors in all modules may disrupt the signature of floral syndromes [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the relationship between modules and pollination syndromes has been found in studies that have determined pollinator effectiveness [ 109 ] and others that have not (e.g., [ 84 ]). Therefore, the lack of an association between modules and syndromes may be related to the presence of super-generalist pollinators in high-elevation environments [ 110 , 111 ]. The presence of these super-generalist floral visitors in all modules may disrupt the signature of floral syndromes [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the wetter and warmer region, higher elevation is typically associated with colder temperatures, imposing harsher conditions for fungal communities (Figure 1). The increases in connectance and nestedness with elevation may be driven by reduced partner availability between bacteria and fungi, owing to decreased fungal species richness (Chesshire et al., 2021). This might require more bacterial generalists to connect with fungal species, which lead to higher nestedness.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the findings of Rezende et al (2007b), our results suggested pollinators might be of even greater importance than plants on nestedness structure in our network. For example, more generalized pollinator species were found likely responsible for higher nestedness (Chesshire et al, 2021).…”
Section: Different Influences Of Phylogenetically Independent and Con...mentioning
confidence: 99%